2020
DOI: 10.1016/j.str.2019.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Dynamics and Functional Implications of Phosphorylated β-Arrestins

Abstract: Highlights d The conformational effects of b-arrestin phosphorylation have been examined d S14D/T276D phospho-mimetic mutation of b-arrestin-2 induced conformational changes d S14D/T276D b-arrestin-2 shows features similar to the preactive state

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…There are several crystallographic structures of both arrestin-2 and arrestin-3. These structures include apo arrestin [40, 44, 47, 50, 51], as well as arrestin bound to clathrin [43], inositol hexaphosphate ( IP6 ) [39, 46], activating peptides [41, 55, 56], and GPCRs [42, 48, 49]. They form three distinct structural clusters, as shown by Figure 3: an apo cluster with the C-tail domain bound to the N-domain, and two distinct active conformations representing the C-tail unbinding and the N-domain and C-domain rotating with respect to each other.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There are several crystallographic structures of both arrestin-2 and arrestin-3. These structures include apo arrestin [40, 44, 47, 50, 51], as well as arrestin bound to clathrin [43], inositol hexaphosphate ( IP6 ) [39, 46], activating peptides [41, 55, 56], and GPCRs [42, 48, 49]. They form three distinct structural clusters, as shown by Figure 3: an apo cluster with the C-tail domain bound to the N-domain, and two distinct active conformations representing the C-tail unbinding and the N-domain and C-domain rotating with respect to each other.…”
Section: Resultsmentioning
confidence: 99%
“…We analyzed a total 26 X-ray structures. Of these, 9 were apo structures, 1 was clathrin-bound, 2 were inositol-6phosphate (IP6) activated structures, 4 were GPCR-activated arrestin structures, and 10 were peptide-activated (Table 1) [39][40][41][42][43][44][45][46][47][48][49][50][51]. Nineteen (19) of the structures were arrestin-2, while 7 were arrestin-3.…”
Section: X-ray Structure Selection and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…These phosphorylation positions are conserved across species. By creating Asp-mutants that mimic one or more of these phosphosites, Kang et al studied their impact on arr conformation via hydrogen-deuterium exchange (HDX) experiments and crystallography [74]. Overall, they found that phosphomimetic mutation of S412 did not have a strong impact on barr-1 conformation and function.…”
Section: Identifying Functional Hot Spots Of Arrestin By Mutagenesismentioning
confidence: 99%